2019
DOI: 10.3389/fpsyg.2019.01495
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Parenting Practices and Psychological Variables of Elite and Sub-Elite Youth Athletes

Abstract: Drawing from the model of parental involvement in sport, the overall purpose was to examine the associations of perceptions of parenting practices (encouragement, reinforcement, instruction, and role modeling) and athletes’ psychological variables (self-efficacy, social self-efficacy, self-regulation, and intrinsic motivation) of elite and sub-elite youth athletes. Participants were elite ( n = 210) and sub-elite ( n = 635) athletes aged between 14 and 18 years ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
1
16
0
5
Order By: Relevance
“…Our findings underlined the importance of psychosocial support from family, friends, and coaches, which has been well documented in previous research with elite athletes (Greenleaf et al, 2001;Brown et al, 2019;Teques et al, 2019;Samuel et al, 2020;Walton et al, 2021). Whilst most athletes indicated a strong sense of support from friends, family, and coaches, levels of organizational support were vastly different for all athletes in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings underlined the importance of psychosocial support from family, friends, and coaches, which has been well documented in previous research with elite athletes (Greenleaf et al, 2001;Brown et al, 2019;Teques et al, 2019;Samuel et al, 2020;Walton et al, 2021). Whilst most athletes indicated a strong sense of support from friends, family, and coaches, levels of organizational support were vastly different for all athletes in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The importance of support from family and friends has been well documented in previous research on elite athlete development (Côté, 1999), performance (Gould & Maynard, 2009;Teques, Calmeiro, Rosado, Silva, & Serpa, 2019) and transitions post career (Brown, Webb, Robinson, & Cotgreave, 2019;Wylleman & Lavallee, 2004). Our findings align with these sentiments, having found that family and friends⎯within and beyond sport⎯provide a crucial social network for athlete wellbeing during the post-Olympic period.…”
Section: Discussionmentioning
confidence: 89%
“…Parents are willing to work with coaches and medical teams to monitor an athlete's activity when out of reach of a coach or when leaving boarding house and returning to live with parents (for example: supervising an athlete' routines to conform to a diet or physical exercise program established by the coach and medical team, supervise an athlete's leisure or playing activities so as not to affect rest time, strive to provide nutritional support (food, drinks, and supplements) for an athlete according to their available funds, and attend training sessions or competitions if needed). Parents are able to manage emotional demands of a competition (for example: not showing behavior that tends to suppress or intimidate an athlete according to their expectations as parents) (Nunomura & Oliveira, 2013;Teques et al, 2019). This parenting is component forms of social integration, instrumental support, information support, and emotional support.…”
Section: Resultsmentioning
confidence: 99%